Cyano resin containing polyhedral oligomeric silsesquioxane structure and preparation method thereof

By introducing a cage-containing silsesquioxane structure into the cyano resin, a cage-shaped framework is formed by using the hydrolysis and condensation reaction of silanes, and cyano functional groups are grafted on the benzene ring, the problems of high water absorption and polarity of traditional resin materials are solved, and higher heat resistance and lower polarity and water absorption are achieved.

CN119775566AActive Publication Date: 2025-04-08XIHUA UNIV +1

Patent Information

Application Number
CN202510264885.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-08
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

Traditional phthalnitrile resins have limited their wider application in multiple fields due to their higher water absorption and higher polarity.

Method used

A cyano resin containing a cage silsesquioxane structure is used, which forms a cage-shaped framework structure with inorganic Si-O-Si bonds through hydrolysis and condensation reaction of silanes, and functional groups containing reactive cyano groups are grafted on an organic benzene ring.

Benefits of technology

The heat resistance, carbon residue and thermal oxygen stability of the material are improved, while reducing its polarity and water absorption, enhancing the overall performance of the resin material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775566A_ABST
    Figure CN119775566A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil wells, in particular to cyano resin containing a cage-shaped silsesquioxane structure and a preparation method of the cyano resin, in the preparation process, a cage-shaped framework structure containing inorganic Si-O-Si bonds is obtained through hydrolytic condensation reaction of silane, and functional groups containing reactive cyano groups are grafted on organic benzene rings on the periphery of the cage-shaped framework structure. A cage-shaped skeleton structure formed by Si-O-Si bonds and heteroaromatic rings (triazine rings and phthalocyanine rings) generated after cyano polymerization are chemical bonds and functional groups with extremely high bond energy and thermal stability, so that the finally prepared material has high heat resistance, high carbon yield and high thermal oxidation stability, and due to the fact that the Si-O-Si bonds are low in polarity and water absorption rate, the material can be used for preparing a high-temperature-resistant material. Therefore, the polarity and the water absorption rate of the final resin material are relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil wells, and in particular to a cyano resin containing a cage-shaped silsesquioxane structure and a preparation method thereof. Background Art

[0002] Phthalonitrile resin, also known as phthalonitrile resin, is produced by the addition polymerization of phthalonitrile resin monomers through cyano groups. It has excellent thermal stability, mechanical properties and excellent processability, and has shown wide application potential in many fields such as aerospace, electronics and electrical, and the automotive industry.

[0003] However, traditional phthalonitrile resins are mostly based on petroleum-based raw materials, which not only brings about environmental pollution problems, but also goes against the current concept of sustainable development. Therefore, the research and development of bio-based phthalonitrile resins using renewable resources as raw materials has become a hot topic in the scientific research field.

[0004] In terms of preparation, some researchers have introduced flexible segments into phthalonitrile monomers, effectively reducing the melting point of phthalonitrile monomers, thereby improving the processing performance of phthalonitrile resins. In addition, some researchers have adopted an organic / inorganic hybrid approach, using phthalonitrile resin as the matrix, and further improved the heat resistance and mechanical properties of composite materials by adding modified particles.

[0005] In general, as a high-performance thermosetting resin, phthalonitrile resin has broad application prospects in many fields. With the continuous deepening of research and continuous improvement of preparation technology, it is believed that it will have even better performance in the future.

[0006] Currently, phthalonitrile resin has high heat resistance and good comprehensive performance, but its high water absorption and high polarity limit its wider application. Summary of the invention

[0007] In order to solve the above technical problems, an embodiment of the present invention provides a cyano resin containing a cage-shaped silsesquioxane structure and a preparation method thereof.

[0008] To achieve the above object, the embodiments of the present invention adopt the following technical solutions: In one aspect, the present invention provides a cyano resin containing a cage-shaped silsesquioxane structure, having the structural formula shown below: , Wherein R2 is selected from any one of the following structural formulas: , , , .

[0009] On the other hand, the present invention provides a method for preparing a cyano resin containing a cage-shaped silsesquioxane structure, comprising the following steps: A. Dissolve silane in benzene to form a solution, then add distilled water and continue stirring, heat the reaction, filter and wash to obtain octaphenyl POSS; B. Nitration of the octaphenyl POSS obtained in step A in a mixed solution of concentrated nitric acid and concentrated sulfuric acid, and precipitation of the reaction solution after the reaction, and suction filtration and drying to obtain nitrated POSS; C. The nitrated POSS and the catalyst in step B are reacted with a cyano-containing monophenol, and then filtered, deslagging, precipitated and repeatedly washed, and dried and solidified to obtain a cyano resin containing a cage-shaped silsesquioxane structure.

[0010] The synthesis reaction equation of one of the cyano resins containing a cage-shaped silsesquioxane structure is shown below:

[0011] Wherein, R1 is chlorine, methoxy or ethoxy, R2 is any one of the above structural formulas, and the first step in the synthesis process is hydrolysis condensation, the chlorine atom forms hydrochloric acid, and the alkoxy group forms an alcohol compound, the second step is the nitration reaction of the benzene ring, and the third step is the condensation reaction of nitric acid and phenolic hydroxyl group, the nitro group is removed to form nitric acid, and nitric acid and carbonate form nitrate.

[0012] In some embodiments, in step A, the silane includes at least one of trichlorophenylsilane, trimethoxyphenylsilane and triethoxyphenylsilane.

[0013] In some embodiments, in step A, the reaction temperature is 80° C. and the reaction time is 3 to 8 hours.

[0014] In some embodiments, in step B, the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 3:1. In some embodiments, in step B, the temperature of the nitration reaction is 50° C. and the time is 2 to 5 hours.

[0015] In some embodiments, in step C, the catalyst is potassium carbonate, and the molar ratio of the catalyst to the nitrated POSS is (8-12):1.

[0016] In some embodiments, in step C, the cyano-containing monophenol includes at least one of 4-hydroxybenzonitrile, 3-hydroxybenzonitrile, 3-hydroxy-4-methylbenzonitrile and 4-hydroxyphthalonitrile, and the molar ratio of the cyano-containing monophenol to the nitrated POSS is (8-12):1.

[0017] In some embodiments, in step C, the reaction temperature is 80-120° C., and the reaction time is 3-10 h.

[0018] Compared with the prior art, the beneficial effect of the present invention is that: in the present invention, a cage-shaped skeleton structure containing an inorganic Si-O-Si bond is first obtained by the hydrolysis condensation reaction of silane, and then a functional group containing a reactive cyano group is grafted onto the organic benzene ring on its periphery. The cage-shaped skeleton structure formed by the Si-O-Si bond and the aromatic heterocyclic ring (triazine ring, phthalocyanine ring) generated after the polymerization of the cyano group are both chemical bonds and functional groups with extremely high bond energy and thermal stability, so the material finally prepared has high heat resistance, residual carbon rate and thermal oxygen stability, and because the polarity and water absorption rate of the Si-O-Si bond are low, the polarity and water absorption rate of the final resin material are low. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The NMR silicon spectrum of the POSS cyano resin synthesized in Example 3; Figure 2 The infrared spectrum of the POSS cyano resin synthesized in Example 3; Figure 3 The scanning electron microscope photograph of Example 3 after polymerization of POSS cyano resin; Figure 4 The TMA test curve after the polymerization of POSS cyano resin is shown in Example 3; Figure 5 The TGA test curve after the polymerization of POSS cyano resin in Example 3 is shown in FIG. Figure 6 Figure a is the combustion heat release curve of Example 2 and Example 3, and Figure b is the combustion heat release curve of the comparative example; Figure 7 This is the tangent value curve of the DMA test of Example 3. DETAILED DESCRIPTION

[0020] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0021] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0022] Example 1

[0023] Trichlorophenylsilane (21.1 g, 0.1 mol) was dissolved in 40 g of benzene at room temperature, and distilled water (9 g, 0.5 mol) was added dropwise with stirring. The mixture was stirred at 80 °C for 5 hours. The reaction system was filtered, rinsed with ethanol and water for 5 times, and dried to obtain octaphenyl POSS. Octaphenyl POSS (10.3 g, 0.01 mol) powder was slowly added to a mixed acid solution of 100 g concentrated nitric acid and concentrated sulfuric acid (the mass ratio of concentrated nitric acid to concentrated sulfuric acid was 3:1) at room temperature, and then the temperature was raised to 50 ° C for reaction for 3 hours. After the reaction, it was slowly cooled to room temperature, and the reaction solution was poured into a large amount of water and stirred for precipitation. It was filtered and washed with a large amount of distilled water, and then dried to obtain nitrated POSS. Nitrated POSS (13.9 g, 0.01 mol) was dissolved in 50 g DMF, potassium carbonate (13.8, 0.1 mol) was added, 3-cyanobenzonitrile (10 g, 0.105 mol) was added, the temperature was raised to 100 ° C for reaction for 5 hours, potassium carbonate was filtered to remove potassium carbonate, the reaction solution was precipitated in a large amount of water, filtered and washed with water for several times, and the target product, a cyano resin monomer containing cage-shaped silsesquioxane, was obtained after drying. The cured product obtained after the resin is cured at 280°C has a glass transition temperature of 351°C, a decomposition temperature of 421°C, a carbon residue rate of 75% at 800°C, a linear expansion coefficient of 13ppm / K at 30-150°C, a dielectric loss tangent of 0.006 at 3GHz, and a saturated water absorption rate of 0.5%.

[0024] The glass transition temperature is obtained by DMA test. The instrument is TA's DMA Q800, using a three-point bending mode, a test frequency of 1Hz, from 30-430℃, 5℃ / min, and the vertex of the tangent curve is taken as the glass transition temperature point. The decomposition is measured by TGA. The instrument is TA's TGA Q50, from 30-800℃, 10℃ / min. The linear expansion coefficient is obtained by TA's TMA Q400 test, compression mode, from 30-350℃, 5℃ / min. The dielectric properties test is carried out in accordance with GB / T 1409, and the water absorption test is carried out in accordance with GB / T 1034.

[0025] Example 2

[0026] Trimethoxyphenylsilane (19.8 g, 0.1 mol) was dissolved in 40 g of benzene at room temperature, and distilled water (9 g, 0.5 mol) was added dropwise with stirring. The mixture was stirred at 80 °C for 4 hours. The reaction system was filtered, rinsed with ethanol and water for 5 times, and dried to obtain octaphenyl POSS. Octaphenyl POSS (10.3 g, 0.01 mol) powder was slowly added to a mixed acid solution of 100 g concentrated nitric acid and concentrated sulfuric acid (the mass ratio of concentrated nitric acid to concentrated sulfuric acid was 3:1) at room temperature, and then the temperature was raised to 50°C for reaction for 4 hours. After the reaction, the reaction solution was slowly cooled to room temperature, poured into a large amount of water, stirred and precipitated, filtered, washed with a large amount of distilled water, and then dried to obtain nitrated POSS. Nitrated POSS (13.9 g, 0.01 mol) was dissolved in 50 g DMF, potassium carbonate (13.8, 0.1 mol) was added, 3-hydroxy-4-methylbenzonitrile (13.3 g, 0.1 mol) was added, the temperature was raised to 100°C for reaction for 8 hours, potassium carbonate was filtered to remove potassium carbonate, the reaction solution was precipitated in a large amount of water, filtered and washed with water for several times, and the target product, a cyano resin monomer containing cage-shaped silsesquioxane, was obtained after drying. The cured product obtained after the resin is cured at 280°C has a glass transition temperature of 332°C, a decomposition temperature of 403°C, a carbon residue rate of 72% at 800°C, a linear expansion coefficient of 18ppm / K at 30-150°C, a dielectric loss tangent of 0.004 at 3GHz, and a saturated water absorption rate of 0.4%.

[0027] Example 3

[0028] Triethoxyphenylsilane (21.2 g, 0.1 mol) was dissolved in 40 g of benzene at room temperature, and distilled water (9 g, 0.5 mol) was added dropwise with stirring. The mixture was stirred at 80 °C for 8 hours. The reaction system was filtered, rinsed with ethanol and water for 5 times, and dried to obtain octaphenyl POSS. Octaphenyl POSS (10.3 g, 0.01 mol) powder was slowly added to a mixed acid solution of 100 g concentrated nitric acid and concentrated sulfuric acid (the mass ratio of concentrated nitric acid to concentrated sulfuric acid was 3:1) at room temperature, and then the temperature was raised to 50°C for reaction for 2 hours. After the reaction, the reaction solution was slowly cooled to room temperature, poured into a large amount of water, stirred and precipitated, filtered, washed with a large amount of distilled water, and then dried to obtain nitrated POSS. Nitrated POSS (13.9 g, 0.01 mol) was dissolved in 50 g DMF, potassium carbonate (13.8, 0.1 mol) was added, 4-hydroxyphthalonitrile (10 g, 0.105 mol) was added, the temperature was raised to 100°C for reaction for 5 hours, potassium carbonate was filtered to remove potassium carbonate, the reaction solution was precipitated in a large amount of water, filtered and washed with water for multiple times, and the target product, a cyano resin monomer containing cage-shaped silsesquioxane, was obtained after drying. The glass transition temperature of the cured product obtained after the resin is cured at 280°C is higher than 400°C, the decomposition temperature is 503°C, the carbon residue rate at 800°C is 76%, the linear expansion coefficient at 30-150°C is 8ppm / K, the dielectric loss tangent value at 3GHz is 0.004, and the saturated water absorption rate is 0.3%.

[0029] Figure 1 The POSS cyano resin NMR spectrum obtained by Example 3 is Figure 1 It can be seen that the single sharp resonance peak at -122 ppm proves that there is only one chemical environment of silicon element in the product, indicating that the obtained cyano resin containing POSS structure has a closed cage-shaped silsesquioxane structure.

[0030] Figure 2 The infrared spectrum of the POSS cyano resin synthesized in Example 3 is as follows: Figure 2 It can be seen that at 2200cm -1 The absorption peak of the cyano-CN triple bond appears at 1500cm -1 The peak at 1200 cm-1 is the benzene ring skeleton stretching vibration absorption peak. -1 The absorption peak of the phenyl ether bond appears at the bottom, which indicates the successful synthesis of the product.

[0031] Figure 3 The scanning electron microscope photo of Example 3 after the polymerization of POSS cyano resin is shown in FIG. Figure 3 It can be seen that since the monomer nature of POSS cyano resin is an organic-inorganic hybrid micro-nano composite particle, it can be seen that the resin has a granular feel after curing.

[0032] Figure 4 The TMA test curve after the polymerization of POSS cyano resin is shown in Example 3. Figure 4 It can be seen that the linear expansion coefficient of the resin can be calculated from the TMA curve, and the heat resistance temperature is higher than the maximum test temperature of 350°C because the glass transition cannot be observed.

[0033] Figure 5 The TGA test curve after the polymerization of POSS cyano resin in Example 3 is shown by Figure 5 It can be seen that its decomposition temperature is 503°C and the residual carbon rate at 800°C is 76%.

[0034] Figure 6 Combustion heat release curves of Example 2, Example 3 and Comparative Example are shown in FIG. Figure 6 Both the data in Table 1 indicate that the introduction of cage-type silsesquioxane (POSS) structure reduces the combustion heat release of the obtained resin material, reduces the heat release capacity, and improves the flame retardant properties.

[0035] Figure 7 is the tangent value curve of the DMA test of Example 3, through Figure 7 It can be seen that no glass transition is observed below 400°C, indicating that its glass transition temperature is higher than 400°C.

[0036] Table 1 Comparison of combustion performance of Example 2, Example 3 and Comparative Example sample Heat release capacity (J / g‧K) Peak heat release (W / g) Total heat release (kJ / g) <![CDATA[Peak exothermic temperature T max (°C)]]> Example 2 9.42 9.5 1.5 446.3 Example 3 3.99 4.0 0.8 319.1 Comparative Example 87.93 89.2 6.7 394 This comparative example is produced by Sichuan Jinxiang Sairui Chemical Co., Ltd., with the brand name PN01, and the structural formula is as follows: .

[0037] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0038] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A cyano resin containing a cage-shaped silsesquioxane structure, characterized in that: It has the following structural formula: , Wherein R2 is selected from any one of the following structural formulas: 、 、 、 。 2. A method for preparing a cyano resin containing a cage-shaped silsesquioxane structure as claimed in claim 1, characterized in that: The following steps are involved: A. Dissolve silane in benzene to form a solution, then add distilled water and continue stirring, heat the reaction, filter and wash to obtain octaphenyl POSS; B. Nitration of the octaphenyl POSS obtained in step A in a mixed solution of concentrated nitric acid and concentrated sulfuric acid, and precipitation of the reaction solution after the reaction, and suction filtration and drying to obtain nitrated POSS; C. The nitrated POSS and the catalyst in step B are reacted with a cyano-containing monophenol, and then filtered, deslagging, precipitated and repeatedly washed, and dried and solidified to obtain a cyano resin containing a cage-shaped silsesquioxane structure.

3. The preparation method according to claim 2, characterized in that: In step A, the silane includes at least one of trichlorophenylsilane, trimethoxyphenylsilane and triethoxyphenylsilane.

4. The preparation method according to claim 2, characterized in that: In step A, the reaction temperature is 80° C. and the reaction time is 3 to 8 hours.

5. The preparation method according to claim 2, characterized in that: In step B, the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 3:

1.

6. The preparation method according to claim 2, characterized in that: In step B, the nitration reaction is carried out at a temperature of 50° C. for a period of 2 to 5 hours.

7. The preparation method according to claim 2, characterized in that: In step C, the catalyst is potassium carbonate, and the molar ratio of the catalyst to the nitrated POSS is (8-12):

1.

8. The preparation method according to claim 2, characterized in that: In step C, the cyanide-containing monophenol includes at least one of 4-hydroxybenzonitrile, 3-hydroxybenzonitrile, 3-hydroxy-4-methylbenzonitrile and 4-hydroxyphthalonitrile, and the molar ratio of the cyanide-containing monophenol to the nitrated POSS is (8-12):

1.

9. The preparation method according to claim 2, characterized in that: In step C, the reaction temperature is 80-120° C., and the reaction time is 3-10 h.

Citation Information

Patent Citations

  • Preparation method of cage-type silsesquioxane-containing low-dielectric cyanate hybrid resin

    CN102079874A

  • Preparation method of bisphthalonitrile polymer containing silsesquioxane POSS structure

    CN108484917A

  • Polyhedral oligomeric silsesquioxane containing cyano and preparation method thereof

    CN108976423A

  • Polyhedral oligomeric silsesquioxane simultaneously containing vinyl and 3-(2, 3-epoxypropoxy) propyl and preparation and application thereof

    CN113461945A

  • POSS (Polyhedral Oligomeric Silsesquioxane) modified bamboo powder reinforced high-ultraviolet-shielding polylactic acid composite material and preparation method thereof

    CN115286909A

Cited By

  • High-temperature-resistant material for coating wing surface of aircraft and preparation method of high-temperature-resistant material

    CN121203541A

  • High-temperature-resistant material for aircraft airfoil coating and preparation method thereof

    CN121203541B